Study of 89 Cases of Peripheral Vascular Disease by CT Angiography - Faruque, M; Islam, AEMM; Haque, S; Islam, MT; Kibria, MG; Hossain, M; Salam, MA; Rahman, F; Hasnat, MA; Khan, HIL Rahman (Cardiovascular Journal, 2011)
Objective: The purpose of this study was to observe the morphological pattern by CT angiography and risk factors for development of peripheral vascular disease in Bangladeshi patient suffering from peripheral vascular disease using a multidetector scanner in the evaluation of patients with peripheral vascular disease. Subject and Method: Eighty nine patients with peripheral vascular disease who were referred for evaluation of peripheral vascular disease underwent CT angiography. We scanned patients from the level of the cerebral arteries to the pedal arteries in a single helical scan. CT angiograms were produced using maximum-intensity-projection, multiplanous reformation and reconstructions. Findings were graded according to nine categories: 1, normal (0% stenosis); 2, mild (1-49% stenosis); 3, moderate (50-74% stenosis); 4, severe (>75% stenosis); 5, tortuosity; 6, aneurysm, 7, calcification, 8, Arteriovenous malformation (AVM), and 9, haematoma. Results: We found Most of the patients in our study were male (69 out of 89 patients). The mean age was 54.49 ±18.36 in male and 49.45 ±17.89 for female. Commonest risk factor in our study was hypertension 46.1%, followed by diabetes 30.3%, family history 27% smoking 23.6%, dyslipidaemia13.5%. Stenosis (5.61%) was the predominate lesion followed by haematoma (4.49%), Arterio –venous malformation (4.49%). Abdominal aorta was mostly affected in the studied population (58.43%) followed by Lower limb (37.08%), Carotid (22.47%), Renal (7.87%) and Upper limb arteries (4.49%). Conclusion: CT angiography is a noninvasive technique for the imaging of peripheral vascular disease. Since no data is available from a well designed study in PVD in our country, till then the data obtained from this study can be used in Bangladesh. Key words: CT angiogram; Peripheral vascular disease (PVD) DOI: http://dx.doi.org/10.3329/cardio.v3i2.9185 Cardiovasc. J. 2011; 3(2): 155-162